Leishmanicidal Activity of Passifloricin A and Derivatives (2004)
ABSTRACT: Several natural and hemisyntetic passifloricins were assayed against Leishmania panamensis amastigotes. High leishmanicidal activity as well as toxicity was observed. The structure of a new compound is also reported.